Impact of Performance Appraisal System on Employee Engagement in Banking Industry: An Empirical Study - Dr. Kiran Raj, Dr. Rajeshwar Dinkar Rahangdale, Dr. Yaduveer Yadav (International Journal of Advanced Science and Technology, 2020)
The Performance appraisal is one of the most significant (HRM) human asset the managerial practices as it yields basic choices necessary to different human asset activities and results. Performance appraisal is the efficient clearing of employees as indicated by their activity and potential turn of events. Performance evaluation has expansive ramifications for mentalities and practices in associations. Responses to appraisal and the evaluation procedure are accepted to essentially impact the adequacy and the general suitability of appraisal frameworks. Recently, employee commitment has gotten expanded consideration from analysts as a significant determinant of representative presentation. The Performance appraisal is fundamentally about what employees need to convey to drive the association’s prosperity. It‘s an opportunity to review results, provide feedback on how results were achieved and confirm expectations. The purpose of the study is to find the role and impact of Performance Appraisal System on Employee Engagement in Banking Industry. The survey includes 288 respondents from the banking industry. It is concluded that most significant effect of performance appraisal system on the employee engagement when the employees says that “Employee’s feedbacks are used for the company’s improvement by the Performance Appraisal System” and it “Changes the behaviour of the employees” and it shows a significant Impact of Performance Appraisal System on Employee engagement.” Keywords: Performance appraisal, Employee’s performance, Employee engagement, Banking Industry.